2014
DOI: 10.1209/0295-5075/107/18003
|View full text |Cite
|
Sign up to set email alerts
|

Mood states modulate complexity in heartbeat dynamics: A multiscale entropy analysis

Abstract: This paper demonstrates that heartbeat complex dynamics is modulated by different pathological mental states. Multiscale entropy analysis was performed on R-R interval series gathered from the electrocardiogram of eight bipolar patients who exhibited mood states among depression, hypomania, and euthymia, i.e., good affective balance. Three different methodologies for the choice of the sample entropy radius value were also compared. We show that the complexity level can be used as a marker of mental states bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 57 publications
(86 reference statements)
4
37
0
Order By: Relevance
“…Moreover, it is important to investigate this coupling in psychiatric as well as neurological disorders which have been shown to involve both cognition and ANS dysfunction [93], and whether its alterations could be a specific marker of mental disorders. According to our findings, we believe that the analysis of EEG θ rhythms will provide a significant decision support tool for managing mental health, also considering the role of insular and pregenual cingulate cortices in psychiatric disorders including mood disorders, panic disorders, obsessive-compulsive disorders, eating disorders and schizophrenia [1,5,46,47,90,94].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, it is important to investigate this coupling in psychiatric as well as neurological disorders which have been shown to involve both cognition and ANS dysfunction [93], and whether its alterations could be a specific marker of mental disorders. According to our findings, we believe that the analysis of EEG θ rhythms will provide a significant decision support tool for managing mental health, also considering the role of insular and pregenual cingulate cortices in psychiatric disorders including mood disorders, panic disorders, obsessive-compulsive disorders, eating disorders and schizophrenia [1,5,46,47,90,94].…”
Section: Discussionmentioning
confidence: 80%
“…However, other authors documented an increase in complexity of systolic arterial pressure in PD patients when compared to controls [32]. In addition, while the physiology underlying complexity-related measures of heartbeat dynamics is still unknown, it is well known that their quantification can provide meaningful information on psychophysiological as well as pathological states [8,10,14,24,39]. In this context, we have previously shown that measures of time-varying complexity provide enhanced discriminatory power when compared to standard complexity measures [36,38], and that the stability and complexity of autonomic dynamics is altered in PD patients when compared to healthy controls as well as within different PD subgroups [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Future developments of devices might include other affective information gathered from the autonomic nervous system dynamics (e.g. [21]), to be also used for clinical applications [22], [23] involving patients with mood or emotional disorders, such as bipolar disorder (e.g., application in [24], [25]). …”
Section: Conclusion and Discussionmentioning
confidence: 99%